2017
DOI: 10.1177/1094670517714059
|View full text |Cite
|
Sign up to set email alerts
|

When Does Customer-Oriented Leadership Pay Off? An Investigation of Frontstage and Backstage Service Teams

Abstract: The service literature highlights the importance of organizational leaders in creating an organization-wide customer orientation (CO). Yet, some open questions remain regarding this relationship: Are organizational leaders from different hierarchical levels equally effective in creating a CO? Does the functional role of employees affect the importance of certain leaders? More generally, when does customer-oriented leadership really pay off? To address these questions, we investigate how senior managers' and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…As a result, the impact of customer orientation coaching on employee performance was reported to be 0.31 coefficient. This result is the same with the results of previous studies, and this hypothesis was confirmed in the Pousa and Mathieu study (2014) and Herhausen et al (2017). H2 suggests that customer orientation coaching has a direct impact on competitor orientation of employee.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As a result, the impact of customer orientation coaching on employee performance was reported to be 0.31 coefficient. This result is the same with the results of previous studies, and this hypothesis was confirmed in the Pousa and Mathieu study (2014) and Herhausen et al (2017). H2 suggests that customer orientation coaching has a direct impact on competitor orientation of employee.…”
Section: Resultssupporting
confidence: 91%
“…The impact of the customer orientation of employee on their performance has been reported to be 0.45. This result is the same with the results of previous studies, and this hypothesis was confirmed in Herhausen et al (2017), Pousa and Mathieu study (2014), Boles et al (2001) and Cross et al (2007). H9 suggests that the sale orientation of employee have a direct impact on their performance.…”
Section: Resultssupporting
confidence: 91%
“…Our literature review emphasizes that, in the limited body of leadership research in the service context, most studies have been conducted in nonvirtual work environments and noncrisis situations (e.g. Wieseke et al , 2011; Benlian, 2014; Herhausen et al , 2017). Consistent with Liao's (2017) statement that the processes and behaviors associated with leading virtual teams to date have been insufficiently investigated, we find barely any work on virtual team leadership in the service context.…”
Section: The Literature and Conceptual Backgroundmentioning
confidence: 99%
“…Social distance is a subdimension of psychological distance, which refers to “the extent of divergence from direct experience of me, here and now along the dimensions of time, space, social perspective, or hypotheticality” (Liberman & Trope, 2014, p. 365). We focus on the social dimension of distance because social distance is central to social identity theory (Ashforth & Mael, 1989), because Joshi and Wakslak (2014) as well as Joshi et al (2016) established a clear association between social distance and the construal level of communication, and because previous research in intraorganizational settings used social distance when investigating construal fit between different “actors” and communication aspects (e.g., Berson & Halevy, 2014; Cole et al, 2009; Herhausen et al, 2017).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Construal level theory further suggests that construal fit determines the effectiveness of organizational communication. The reason is that construal fit increases psychological engagement (Berson & Halevy, 2014), enhances perceived credibility of information (Hansen & Wanke, 2010), intensifies emotional reactions to messages (Lee et al, 2009), and makes communication from a specific source more effective (Herhausen et al, 2017). The combined action of these mechanisms should enhance the effectiveness of organizational communication.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%